(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: To find the effectiveness of cognitive therapy in post-menopausal women. Method: The study group consisted of 50 post-menopausal women, aged between 45-65 years, screening of 100 women was done and 50 women having cognitive changes and fulfilling the inclusion and exclusion criteria were selected. They were given exercises for 4 weeks,4 times per week and pre-post result were calculated on the basis of attention, memory, anxiety and depression. The scores were measured by using mini mental scale, mood scale and Hamilton depression rating scale. Conclusion: The results demonstrated that there is statistically extremely significant difference in cognitive changes in post menopausal women. (p >0.0001)